FURIN Inhibition Reduces Vascular Remodeling and Atherosclerotic Lesion Progression in Mice. Issue 3 (March 2019) - Yakala, Gopala K.; Cabrera-Fuentes, Hector A.; Crespo-Avilan, Gustavo E.; Rattanasopa, Chutima; Burlacu, Alexandrina; George, Benjamin L.; Anand, Kaviya; Mayan, David Castaño; Corlianò, Maria; Hernández-Reséndiz, Sauri; Wu, Zihao; Schwerk, Anne M.K.; et al.
Abstract : Objective—: Atherosclerotic coronary artery disease is the leading cause of death worldwide, and current treatment options are insufficient. Using systems-level network cluster analyses on a large coronary artery disease case-control cohort, we previously identified PCSK3 (proprotein convertase subtilisin/kexin family member 3; FURIN ) as a member of several coronary artery disease–associated pathways. Thus, our objective is to determine the role of FURIN in atherosclerosis. Approach and Results—: In vitro, FURIN inhibitor treatment resulted in reduced monocyte migration and reduced macrophage and vascular endothelial cell inflammatory and cytokine gene expression. In vivo, administration of an irreversible inhibitor of FURIN, α-1-PDX (α1-antitrypsin Portland), to hyperlipidemic Ldlr −/− mice resulted in lower atherosclerotic lesion area and a specific reduction in severe lesions. Significantly lower lesional macrophage and collagen area, as well as systemic inflammatory markers, were observed. MMP2 (matrix metallopeptidase 2), an effector of endothelial function and atherosclerotic lesion progression, and a FURIN substrate was significantly reduced in the aorta of inhibitor-treated mice. To determine FURIN's role in vascular endothelial function, we administered α-1-PDX to Apoe −/− mice harboring a wire injury in the common carotid artery. We observed significantly decreased carotid intimal thickness and lower plaque cellularity, smooth muscle cell, macrophage, and inflammatory marker content, suggesting protection against vascular remodeling. Overexpression of FURIN in this model resulted in a significant 67% increase in intimal plaque thickness, confirming that FURIN levels directly correlate with atherosclerosis. Conclusions—: We show that systemic inhibition of FURIN in mice decreases vascular remodeling and atherosclerosis. FURIN-mediated modulation of MMP2 activity may contribute to the atheroprotection observed in these mice. Abstract : Supplemental Digital Content is available in the text.